The Effects Of The Family Ownership Structure On The Relationship Between Board Of Directors And Earnings Quality: Evidence Manufacturing Firms In Amman Stock Exchange - Tareq Mohammad Almomani; Abdullah Mohammed Ayedh; Mohammad Abdallah Almomani (Science and Engineering Research Support Society, 2024)
Indexed by ERA